2014
DOI: 10.1016/j.jcyt.2013.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Open-label, multi-center, non-randomized, single-arm study to evaluate the safety and efficacy of dendritic cell immunotherapy in patients with refractory solid malignancies, on supportive care

Abstract: Therapy was safe. The responses, time to treatment progression and survival are encouraging for patients with aggressive refractory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…The initial surge in PSA may be attributed to the heightened immune response, observed in various other studies. 32) The PSA values did not correlate with the response as SD and PR patients also showed surge in day 15 and day 60 values of PSA. All patients showed a positive DTH response against the TAA used for priming the DC.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The initial surge in PSA may be attributed to the heightened immune response, observed in various other studies. 32) The PSA values did not correlate with the response as SD and PR patients also showed surge in day 15 and day 60 values of PSA. All patients showed a positive DTH response against the TAA used for priming the DC.…”
Section: Discussionmentioning
confidence: 92%
“…Samples were analyzed on use of a flow cytometer (FACS Calibur, Becton Dickinson, U.S.A.). Ratio of CD4+ and CD8+ Cells Analysis of CD4 and CD8 lymphocyte count was performed according to the procedure earlier described by Bapsy et al 32) Briefly 2-3 mL of peripheral blood was incubated with the following antihuman monoclonal antibodies: anti-CD3-PC5, anti-CD4-FITC, anti-CD8-PE and anti-CD16-FITC (Becton Dickinson). After immunofluorescent staining, the cells were fixed with 1% paraformaldehyde and were then analyzed by means of a FACSCalibur flow cytometer with the use of CellQuest-PRO software (Becton Dickinson).…”
Section: Patient Population and Study Designmentioning
confidence: 99%
“…[81] APCEDEN is a formulation of dendritic cells used in this study and is derived from CD14+ monocytes, which is further described in Romani et al [87] Bapsy et al concluded that the APCEDEN therapy leads to no major toxicity and is safe. Patients who were classified as responders had a median OS of 397 days and a significant improvement in quality of life, justifying the need for advanced development and randomized control trials.…”
Section: Uses In Pdac Therapy and Outcomesmentioning
confidence: 92%
“…The DCs can then be pulsed with the target ligand and activated using TNF-alpha. [79,[81][82][83][84] …”
Section: Production Of Dendritic Cellsmentioning
confidence: 99%
See 1 more Smart Citation